Government or Donor: The Budget for HIV/AIDS Control and Financial Commitment in Bandung City, Indonesia - Mambea, Indra Yudha; Prawiranegara, Rozar; Maharani, Febrina; Vadra, Jorghi; Siregar, Adiatma Y M; Bijlmakers, Pande Leon (Kesmas, 2023)
The number of HIV/AIDS cases in Indonesia has steadily increased since 1987. West Java Province, especially Bandung City, had the highest HIV/AIDS cases among other districts/cities in 2016. Some stakeholders' interventions overlap with others, leading to inefficient use of the limited government budget and flattening international donor funding. This study aimed to estimate the HIV/AIDS budget in Bandung City and then segregate the share of the budget by funding source and objectives. This study was a part of the Priority Setting Involving Stakeholder Using Multiple Criteria (PRISMA) project in 2017 to prioritize HIV/AIDS interventions knowing that Bandung City had the highest HIV/AIDS cases. Data from several institutions and relevant budget allocations were obtained before (2016) and after (2018-2019) the PRISMA project. HIV/AIDS control programs in Bandung City largely depend on international funding: 49% in 2016 (~USD208,898), 85% in 2018 (~USD386,132), and 71% in 2019 (~USD389,943) for a total of ~USD1,433,216. The largest budget was allocated to core interventions, with prevention dominating the budget since 2018. The budget allocated for prevention increased significantly from 2016-2019, most likely under the influence of the PRISMA project.